Accuracy of Hysterosalpingography as a Screening Test for Evaluating Infertility (Bangladesh Journal of Radiology and Imaging, 2026)
Background: The aim of this study was to evaluate the accuracy of hysterosalpingography (HSG) for evaluating infertility. Objective: To measure the sensitivity & specificity of hysterosalpingography as a screening test to assess the uterine cavity & fallopian tubes of infertile patients. Methodology: A total of 100 adult subjects were selected in a private diagnostic center in Cumilla referred to radiology department from gynecologist private practice. Data for the present investigation were collected via an interviewer administered questionnaire, which included questions on clinical & past medical history, drug history and also findings of HSG report, laparoscopy report were collected. Accuracy, sensitivity & specificity values of HSG in the diagnosis of uterine & tubal pathology were calculated by appropriate statistical formula. Here laparoscopic findings are the gold standard. Result: HSG showed a sensitivity of 80% compared with that of laparoscopy and a specificity of 78.12%, with a positive predictive value of 88.7% and a negative predictive value of 65.7% with accuracy about 80%. Conclusion: HSG is still a useful screening test for the evaluation of the uterine cavity in the study of primary or secondary infertility. In addition, HSG provides information concerning the assessment of tubal morphology and patency. We believe that these two procedures are complementary in the evaluation of the uterine cavity